Getting SEQ moving: 2011-2012 National, State, Regional and Local Infrastructure Priorities ; The Council of Mayors (SEQ) Submission. - Council of Mayors South East Queensland; South East Queensland Council of Mayors (Brisbane, Qld. : Council of Mayors, 2011)
"Identifies five priority programs: National Significance; State and Regional Significance; Rail Network; Active Transport Network; and Public Space Renewal. This submission provides a comprehensive pipeline of infrastructure projects that are informed by Federal and State Government policy settings and are of national, state, regional and local significance." - foreword.
Title from PDF cover page (viewed on Dec. 10, 2012)
Text and graphics.
Also available online (as at 10/12/2012) at http://www.councilofmayorsseq.qld.gov.au/News/Publications.aspx.
Keywords: City planning -- Australia -- Queensland, South East; City planning -- Queensland, South East; City planning -- Queensland, Southeast; Infrastructure (Economics) -- Australia -- Queensland, South East -- Finance; Infrastructure (Economics) -- Australia -- Queensland, South East -- Planning; Infrastructure (Economics) -- Australia -- Queensland, South East; Infrastructure (Economics) -- Queensland, South East -- Finance; Infrastructure (Economics) -- Queensland, South East -- Planning; Infrastructure (Economics) -- Queensland, South East; Infrastructure (Economics) -- Queensland, Southeast -- Finance; Infrastructure (Economics) -- Queensland, Southeast -- Planning; Infrastructure (Economics) -- Queensland, Southeast; Regional planning -- Australia -- Queensland, South East; Regional planning -- Queensland, South East; Regional planning -- Queensland, Southeast; Transportation -- Australia -- Queensland, South East -- Finance; Transportation -- Australia -- Queensland, South East -- Planning; Transportation -- Queensland, South East -- Finance; Transportation -- Queensland, South East -- Planning; Transportation -- Queensland, Southeast -- Finance; Transportation -- Queensland, Southeast -- Planning; City planning; Infrastructure (Economics); Infrastructure (Economics) -- Finance; Infrastructure (Economics) -- Planning; Planning; Regional planning; Transportation -- Finance; Transportation -- Planning; Queensland, South East -- Planning; Queensland, Southeast -- Planning; Australia -- Queensland, South East